Treating Beyond Pockets- an unusual Case of Central Ossifying Fibroma and its Management - Tambe, Lashika Vasant; Gaikwad, Rajesh; Kende, Prajwalit; Kazi, Noaman (Indian Journal of Case Reports, 2019)
Periodontal pocket and teeth mobility are common symptoms of patients having periodontitis. Although there are several reasons for teeth mobility, one of the reason is an odontogenic and non-odontogenic tumor. An ossifying fibroma is a rare benign fibro-osseous neoplasm of the jaw characterized by the substitution of normal bone by fibrous tissues and newly formed calcified products such as bone, cementum or both. This case report describes an unusual case of tooth mobility and swelling in mandibular anterior teeth region with respect to 31, 32 and 33 teeth of a 28 year-old female patient.Initially, the clinical symptoms were suggestive of the periodontal pocket. However, the radiographical, surgical and histological findings confirmed the diagnosis of Central ossifying fibroma. Controversies regarding the terminology and classification along with the differential diagnosis are discussed and a review is provided of the literature on the subject.